IMPROVING LEARNING OUTCOMES THROUGH APPLICATION OF MODEL QUANTUM TEACHING - Ruminingsih, Ruminingsih; admin, admin (Publikasi dan UKI Press UKI Toraja., 2022)
Student learning outcomes in subjects at SMPN 5 Panggarangan are still relatively low, this is because the learning model used is stillteacher centered, lack of maximizing student potential, without giving students an active role in learning. This study aims to improve the learning outcomes of students at SMPN 5 Panggarangan by using the quantum teaching. This type of research is a collaborative Classroom Action Research (CAR). The research subjects were students at SMPN 5 Panggarangan, totaling 37 students. The instruments used are observation sheets and tests. Observational data were analyzed descriptively qualitatively and data from the test results were analyzed descriptively quantitatively. The results of the pre-action research showed that students' learning outcomes in were low. The average value of the new class reached 64.21 and the percentage of completeness was 40.54%. After doing the action using the quantum teaching that varies various learning methods in cycle I, value class average increased to 68.70 and the percentage of completeness increased to 62.16%. Likewise after the improvement of Quantum Teaching which is accompanied by encouragement to actively ask questions, give feedback, reinforcement, and the distribution of heterogeneous groups in the action cycle II, further enhances students' learning outcomes. The class average value increased to 76.76 and the percentage of completeness increased to 94.59%.